REKONSTRUKSI PEMAHAMAN PENILAIAN PEMBEJALARAN: GUGATAN TERHADAP UJIAN NASIONAL PENDIDIKAN KESETARAAN - Agus Sadid (Jurnal Paedagogy, 2015)
Assessment in learning has a very important meaning, because from the assessment activities we can determine and know the results of children's learning development (read: learning citizens) during the learning process. Assessment is part of evaluation activities that must exist in both formal and non-formal education. This paper examines some of the tutors' misconceptions about assessment, especially alternative assessment concepts, authentic assessments and written tests (paper-and-pencil tests). Assuming that conventional written tests cannot fulfill the need to obtain accurate and comprehensive information about the competence of learning citizens, tutors are encouraged to implement alternative assessments. However, the alternative assessments were not well understood by the tutors in terms of their roles, objectives, and ways of implementing them. Therefore, in order to provide insight into the concept of comprehensive assessment, this paper explores the issue of alternative assessment and compares it to conventional tests in order to make clear its role and function in education, along with the advantages and disadvantages of each. Some of the tutors' misconceptions about the assessment are described and discussed so that the understanding of the assessment concept can be corrected, so that in the end the tutors are not trapped in understanding the concept of assessment limited to conventional assessment (call it: written test)